Obstacle Detection with the Long Cane: Effect of Cane Tip Design and Technique Modification on Performance. (September 2018) - Kim, Dae Shik; Emerson, Robert Wall
Introduction: The purpose of this study was to investigate the effect of cane tip design and cane technique modification on obstacle detection performance as they interact with the size, height, and position of obstacles. Methods: A repeated-measures design with block randomization was used for the study. In experiment one, participants attempted to detect obstacles with either a marshmallow tip or a bundu basher tip. In experiment two, participants were asked to detect obstacles using either the constant-contact technique or a modified constant-contact technique. Results: As predicted, the obstacle detection rate with the bundu basher tip (M = 66.1%, SD = 7.4%) was significantly higher than that with the marshmallow tip (M = 54.6%, SD = 6.8%), F(1, 11) = 24.19, p, r = .83. However, contrary to our hypothesis, the obstacle detection rate with the modified constant-contact technique (M = 56.0%, SD = 7.4%) was significantly lower than that with the constant-contact technique (M = 61.3%, SD = 5.2%), F(1, 13) = 6.49, p = .024, r = .58. In addition, participants detected the obstacles that were positioned at the center of their walking path (M = 61.9%, SD = 6.6%) at a significantly higher rate than those positioned slightly off to the side (M = 55.4%, SD = 7.3%), F(1, 13) = 10.73, p = .006, r = .67. Discussion: A bundu basher tip was more advantageous than the marshmallow tip for detecting obstacles. Implications for practitioners: Given the findings of the study, cane users and orientation and mobility (O&M) specialists should consider using or recommending a bundu basher tip (or a similar tip that has an increased contact area with the walking surface), particularly when the traveling environment often presents unexpected obstacles that may trip the cane user.